Closed-Loop Utilization of Molten Salts in Layered Material Preparation for Lithium-Ion Batteries - Chen, Zhanjun; Wang, Tao; Guo, Jun; Zhong, Hongbing; Hu, Chuanyue; Zhao, Ruirui; Chen, Hongyu (Frontiers in Energy Research, 2021)
Molten-salt assisted solid-state synthesis is considered a promising method in obtaining layer-structured cathodes for lithium-ion batteries with homogeneous elemental distribution and controllable morphologies. However, drawbacks like resource wasting arisen from redundant salt removal after sintering greatly hinder the broader application of this technique. In this paper, a closed-loop utilization of molten salts is proposed for the first time with specific electrochemical properties of the products studied. Results confirm the feasibility of this strategy that with only replenishing LiOH, the recycled LiOH-LiCl molten salts can be successfully reused into LiNi0.5Co0.2Mn0.3O2 synthesis, which exhibits compatible electrochemical performance with pristine one. We believe this research can provide significant insight in guiding green and environmental-friendly preparation ways where molten salts are involved.